Ixodofauna of the city of Stavropol - N. A. Koshkina; V. I. Kolesnikov; M. N. Vasilchenko (Российский паразитологический журнал)
On the territory of Stavropol city formed habitats of two species of ixodid ticks: Ixodes ricinus and Dermacentor pictus. I. ricinus are the most distributed